2022
DOI: 10.1037/com0000312
|View full text |Cite
|
Sign up to set email alerts
|

A modified version of the dimensional change card sort task tests cognitive flexibility in children (Homo sapiens) and cotton-top tamarins (Saguinus oedipus).

Abstract: A modified Dimensional Change Card Sort (DCCS) task was used to test cognitive flexibility in adult cotton-top tamarins and children aged 19 months to 60 months. Subjects had to infer a rule from the experience of selecting between two cards to earn a reward, and the pairs of stimuli defined the rule (e.g., pick blue ones, not red ones, or pick trucks, not boats). Two different tests measured subjects’ ability to shift to a reversal of the rule (intradimensional shift) and to shift to a new rule defined by a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 52 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…In this issue's featured article, Neiworth et al (2022) report that they have conducted exactly this kind of comparative study: They examined cognitive flexibility in adult cotton-top tamarins (Saguinus oedipus) and human children in three age groups (,3 years, 3-4 years, and 4-5 years) as they participated in a modified version of the DCCS (Figures 1 and 2). Neiworth et al (2022) reasoned that cotton-top tamarins, which live in socially cohesive monogamous family groups, and in which both parents and adult offspring share caring for young infants, are likely candidates to possess cognitive flexibility. A body of work with this endangered primate (e.g., Neiworth et al, 2001Neiworth et al, , 2002Neiworth et al, , 2009Neiworth, 2013) has shown that they demonstrate relatively heightened social awareness compared to other nonhuman primates.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue's featured article, Neiworth et al (2022) report that they have conducted exactly this kind of comparative study: They examined cognitive flexibility in adult cotton-top tamarins (Saguinus oedipus) and human children in three age groups (,3 years, 3-4 years, and 4-5 years) as they participated in a modified version of the DCCS (Figures 1 and 2). Neiworth et al (2022) reasoned that cotton-top tamarins, which live in socially cohesive monogamous family groups, and in which both parents and adult offspring share caring for young infants, are likely candidates to possess cognitive flexibility. A body of work with this endangered primate (e.g., Neiworth et al, 2001Neiworth et al, , 2002Neiworth et al, , 2009Neiworth, 2013) has shown that they demonstrate relatively heightened social awareness compared to other nonhuman primates.…”
mentioning
confidence: 99%
“…If the hypothesis of shared processes supporting cognitive flexibility and social awareness is correct, tamarins might be expected to master interdimensional shifts in an abstract task such as the DCCS. On the other hand, Neiworth et al (2022) noted that tamarins display other aspects of cognition that suggest limited rule-shifting capacity.…”
mentioning
confidence: 99%
See 3 more Smart Citations